Quality of Audit Services As A Factor of Increase in The Trust Level of The Targeted Users in The Financial Statements - Sergiu ȘOIMU; Galina BADICU; Veronica GROSU; Svetlana MIHAILA (Communications of International Proceedings, 2022)
In the context of the rapid diversification and renewal of the service offer, the globalization of markets, the continuous increase in customer demands, the quality of audit services has become a determining factor in the competitiveness of entities. After numerous spectacular financial scandals in the world, an international dispute arose about the quality of audit services, as well as the need to increase the level of audit quality of financial statements. At the same time, considering the worldwide pandemic of coronavirus disease, the quality of audit services becomes even more important due to the multiple implications that the crisis can have on the entities' financial statements. Given the fact that user confidence is conditioned by the perception of a quality of audit services that meets its reasonable requirements, it is essential that auditors, competently and in compliance with the rules of audit and ethics standards, maintain a high level of quality. Based on this premise, this paper aims to review the relevant literature related to the quality of audit services, allowing authors to record a number of aspects that demonstrate that the quality of audit services is a factor in increasing the degree of trust of the targeted users in the financial statements.
Keywords: audit; quality of audit services; degree of trust of users; professional skepticism; professional ethics; professional reasoning; the COVID-19 pandemic.